The influence of oxidation on the tribological performance of diester lubricant. (3rd July 2013) - Wu, Yanxia; Li, Weimin; Wang, Xiaobo
ABSTRACT The oxidative degradation test of di‐2‐ethylhexyl sebacate (DEHS) was carried out by a sealed stainless steel reactor. Fourier transform infrared spectroscopy and gas chromatography–mass spectrometry (GC–MS) were utilised to characterise the chemical composition and molecular structure of the oxidation products. The results revealed that 2‐ethyl‐1‐hexanol and mono(2‐ethylhexyl)sebacate were major degradation products in the liquid phase. Tribological behaviour was measured using a four‐ball tester. Scanning electron microscopy was employed to investigate the morphologies of the worn surface. Tribological results showed that anti‐wear and friction‐reducing performances of DEHS were highly dependent on the chemical composition of the oxidation products generated during the test. The hydroperoxides formed during the initial oxidation process could deteriorate lubrication properties of DEHS. However, certain amount of highly polar degradation products (acids and alcohols) generated could significantly improve the friction‐reducing performance of DEHS by the formation of boundary adsorption films on the rubbing surfaces. Copyright © 2013 John Wiley & Sons, Ltd.